Genome-wide identification and expression analysis of the U-box E3 ubiquitin ligase gene family related to salt tolerance in sorghum (Sorghum bicolor L.) - Cui, Jianghui; Ren, Genzeng; Bai, Yuzhe; Gao, Yukun; Yang, Puyuan; Chang, Jinhua (Frontiers in Plant Science, 2023)
Plant U-box (PUB) E3 ubiquitin ligases play essential roles in many biological processes and stress responses, but little is known about their functions in sorghum (Sorghum bicolor L.). In the present study, 59 SbPUB genes were identified in the sorghum genome. Based on the phylogenetic analysis, the 59 SbPUB genes were clustered into five groups, which were also supported by the conserved motifs and structures of these genes. SbPUB genes were found to be unevenly distributed on the 10 chromosomes of sorghum. Most PUB genes (16) were found on chromosome 4, but there were no PUB genes on chromosome 5. Analysis of cis-acting elements showed that SbPUB genes were involved in many important biological processes, particularly in response to salt stress. From proteomic and transcriptomic data, we found that several SbPUB genes had diverse expressions under different salt treatments. To verify the expression of SbPUBs, qRT-PCR analyses also were conducted under salt stress, and the result was consistent with the expression analysis. Furthermore, 12 SbPUB genes were found to contain MYB-related elements, which are important regulators of flavonoid biosynthesis. These results, which were consistent with our previous multi-omics analysis of sorghum salt stress, laid a solid foundation for further mechanistic study of salt tolerance in sorghum. Our study showed that PUB genes play a crucial role in regulating salt stress, and might serve as promising targets for the breeding of salt-tolerant sorghum in the future